Tokens and Social Life in Roman Imperial Italy - Rowan, Clare (Cambridge University Press, 2024)
This is a unique and accessible introduction to an underutilised source, Roman tokens, with a focus on those found in Imperial Italy. It explains how tokens can illuminate all kinds of issues such as identity, entertainment, euergetism, imperial ideology, festivals, material culture and everyday life.